Opening remarks of the Sixth Biennial International Conference on Mathematics and Computation in Music (MCM 2017) in Mexico City, June 26–29, 2017. Issue 1 (2nd January 2018) - Lluis-Puebla, Emilio
Abstract : This is an edited transcript of my opening remarks at MCM 2017. In the opening address, I presented a short summary of the last three decades of the field, mathematically speaking, and gave a brief description of how it began and what has been done. The website of the conference ishttp://www.mcm2017.org/ .